The Role of Religious Counselors in Fostering Kampong Moderation in Subulussalam City - Hanum OK, Azizah; Arsyad, Junaidi; Amri, Khairul (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
This research explores the role of Islamic religious instructors in fostering religious moderation in the villages of Subulussalam City, particularly in Suka Makmur and Penanggalan villages. The aim is to understand how religious extension workers promote harmonious socio-religious harmony in diverse communities. Using a qualitative approach and a multi-site study design, the research involved semi-structured interviews, participatory observation, and document analysis to collect data from religious extension workers, community leaders, and community members. The results show that the role of religious educators as motivators, agents of change, central figures, and facilitators is crucial in maintaining and enhancing inter-religious harmony and cooperation. Activities such as joint construction of houses of worship, joint religious celebrations, and gotong royong show the community's high level of religious moderation. These findings suggest that the religious moderation model implemented in Suka Makmur and Penanggalan villages can be used as a reference for similar programs in other areas, strengthening the role of religious educators in promoting socio-religious harmony.